(untitled) (Colombia Medica, 1990)
To know the current status of blenorrhagia in high-risk groups, the prevalence of Neisseria gonorrhoeae was measured in 214 women attending the Barrio Obrero Health Center in the city of Cali, Colombia, for the control of sexually transmitted diseases. Measurement was done by two methods: 1) the Gonozyme enzymatic test that detects the gonococcal antigen, showed a prevalence of 19.3%; 2) culture in three different media: modified Thayer-Martin agar, traditional Thayer-Martin agar, and chocolate agar with VCN. The first medium yielded 48 isolates, with a prevalence of 22.4%. Of the 48 isolates, 13 (27.1%) produced beta-lactamase.